PENDIDIKAN KETERAMPILAN PERDAMAIAN DAN RESOLUSI KONFLIK BAGI SISWA SMA SEKOLAH KRISTEN SATYA WACANA, SALATIGA - Pattinussa, Jhon Maxwell Yosua; Arlan, Adri; Indrasari, Karina Putri (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
Indonesia as a large and diverse nation requires peace. The diversity found within Indonesia must be continuously preserved and managed well to avoid conflict and division. Therefore, Indonesian society needs to be equipped with skills and awareness in managing diversity. A tangible action that can be taken is to implement this idea by organizing peace education and conflict resolution training across various sectors of society. As the primary target of this training, teenagers such as students from Satya Wacana Christian High School are the future leaders of the nation and play a significant role in the future, so they need to be equipped with knowledge and skills in peace and conflict management. Satya Wacana Christian High School is a Christian school located in a heterogeneous environment, which creates opportunities for conflict or friction due to the differences that always exist in society. This makes Satya Wacana Christian High School considered an appropriate partner in conducting peace education and conflict resolution training. The community service activities are carried out in the form of interactive and participatory training facilitated by lecturers and students using peace education modules based on Christian and Biblical values. The training aims to equip students with skills and insights into peace in order to live out their identity as agents of Christ's peace. Through the community service activities conducted by the PkM Youth & Peace Project team under the International Relations Study Program of FISIP UPH, it is hoped that students of Satya Wacana Christian High School will be able to actively participate, starting from themselves, in preventing potential conflicts in their immediate environment, for the sake of peace in Indonesia.